Identification of Sentinel Lymph Node in Breast Cancer with three Tracers (Radiocolloid, Methylene blue, and Indocyanine Green). (Case Report) - Kondov, Goran Borislav; Gruev, Viktor; Stojanovski, Sinisha; Bogdanovska-Todorovska, Magdalena; Colanceski, Risto; Srceva, Marija; Jovanovska, Anamarija; Stojkovski, Zlatko; Kondov, Goran (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Sentinel lymph node (SNL) biopsy in breast cancer for the determination of axillary status is standard procedures in surgical treatment of early-stage breast cancer. The identification of the SNL is usually performed by radiocolloid injection or/and injection of methylene blue due. The use of indocyanine green (ICG) dye, which is fluorescent dye, which movement in breast and axillar pit, can be followed with special cameras which detect near infrared specatar of light. CASE REPORT: In this paper, we present case report of patient with breast cancer, where we perform SNL detection with three methods: Use of radiocolloid which we trace with static gamma camera, and intraoperatively with hand held gamma probe, methylene blue dye which movement we followed by eye contact and using indocyanine green which movement was followed by specially constructed multispectral camera, which can detect near-infrared fluorescence that is emitted by ICG and methyline blue, respectively. CONCLUSION: Fluorescent imaging with ICG is a sensitive, valuable, and safe method for SNL biopsy. Finding new agents that would identify the SNL, especially if they are not radioactive would be an important step in wider application of this method.